EFFECTS OF FENUGREEK SEED ON HEPATIC CELLULAR FUNCTION'S IN LAYING HENS - AL-Qayim, M. A. (The Iraqi Journal of Veterinary Medicine, 2000)
The seeds of Trigonella foenum graecum (Fenugreek) was fed to laying hens at dietary level of 6% for 28 days. FG seeds generally had no toxic effects as evidence by normal liver function tests. Histological examination of liver sections from FG seeds fed hens (groupT) lack of any histopathological changes as compared with hens fed basal diet (groupC), and the activities of plasma transaminases enzymes were not altered. On the other hand the plasma level of ALP enzyme significantly increased under the effects of feeding FG seeds. Plasma sugar of groupT revealed a significant elevation correlated with a decrease in plasma proteins. The results of the present work indicate a nontoxic effect of FG seeds on hepato cellular function